Identifikasi Tingkat Kematangan Buah Strawberry Berdasarkan Warna RGB dengan Menggunakan Metode Regionprops - Sari, Bella Maya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The traditional fruit identification process experiences many obstacles due to human nature which has weaknesses that make the desired results ineffective. Advances in computer technology have touched the world of agriculture from a pre-harvest and post-harvest perspective. Here the problem arises how to recognize the fruit so that it fits the real conditions. The condition of the strawberry fruit is determined by the level of maturity seen from the color side of the strawberry. Farmers usually classify strawberries into ripe, medium ripe and raw categories. Image processing method has the ability to analyze maturity conditions using Red, Green, Blue (RGB) values ​​as a reference. Determination of classification using the Regionprops method which uses the value on the matrix label as a reference. The results in this study amounted to 60%. So it can be concluded that the Regionprops method can be used for the identification process of fruit.